Potential of Jamu in Nanotechnology Perspective as an Alternative Treatment for Covid-19 - Kurniawan, Dhadhang Wahyu; Ikhsanudin, Azis (Pharmaceutical Sciences and Research, 2020)
The world seems to be recovering at this time, especially because of the 2019 global coronavirus disease pandemic (COVID-19) caused by the Coronavirus 2 virus (SARS-CoV-2). This virus is similar to other β-coronaviruses through several steps to enter and bind angiotensin-converting enzyme 2 (ACE2) as the main receptor. This binding, particularly in the respiratory epithelium and alveoli of the lungs, affects harmony in human host cells. No specific vaccines and antivirals are available to date as drug investigations are still ongoing. However, many Indonesians consume herbal medicine, especially 'empon-empon' containing the Zingiberaceae family, to protect their health from COVID-19. So far, herbal medicine has shown good results to protect the Indonesian people in fighting SARS-CoV-2 empirically. In this review, we describe the characteristics of SARS-CoV-2, herbal ingredients that are active in fighting COVID-19, and applied nanotechnology challenges to COVID-19. Therefore, it is proposed to develop herbal medicine with a nanotechnology approach to increase the efficacy and potential of herbal medicine in fighting COVID-19. Moreover, the development of nanotechnology for Indonesian jamu will increase the value of Indonesian jamu and raise its reputation in the world.